2011
DOI: 10.1021/jp200462h
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of a Water Wire in a Hydrophobic Peptide Channel with an Aromatic Lining

Abstract: A one-dimensional water wire has been characterized by X-ray diffraction in single crystals of the tripeptide Ac-Phe-Pro-Trp-OMe. Crystals in the hexagonal space group P6(5) reveal a central hydrophobic channel lined by aromatic residues which entraps an approximately linear array of hydrogen bonded water molecules. The absence of any significant van der Waals contact with the channel walls suggests that the dominant interaction between the "water wire" and "peptide nanotube" is electrostatic in origin. An ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…To overcome these problems, bortezomib analogues are targeted [18]. The peptide based vaccine Nano vaccine adjuvants, and aromatic peptides and beta amino acids are better tool of cancer treatment [19][20][21][22][23][24][25].…”
Section: Side Effects Of Bortezomibmentioning
confidence: 99%
“…To overcome these problems, bortezomib analogues are targeted [18]. The peptide based vaccine Nano vaccine adjuvants, and aromatic peptides and beta amino acids are better tool of cancer treatment [19][20][21][22][23][24][25].…”
Section: Side Effects Of Bortezomibmentioning
confidence: 99%
“…These reports sparked a flurry of activity on the conformational properties of β peptide oligomers. An early study from Appavu et al [3][4][5][6][7], had demonstrated that unsubstituted β and γ amino acid residues can be incorporated into oligopeptide helices, without disturbing the overall helical fold [4].…”
Section: H-n I+3mentioning
confidence: 99%
“…Thus, both β-turn and 3 10 /α-helical structures can readily accommodate the Ac 6 c residue. Two β amino acid homologs may be considered viz β 2,2 Ac 6 c, and β 3,3 Ac 6 c. Earlier studies from this laboratory focused on the more readily synthetically accessible residue β 3,3 Ac 6 c. 3,4,5,6,7,8 X-ray crystallographic characterization of a…”
Section: β-Amino Acid Residuesmentioning
confidence: 99%
“…Other studies on peptide hairpins containing interacting Phe residues clearly indicate that the energy of interaction of Phe-Phe pairs is about -0.5 kcal/mol compared to its Cha analog [7][8][9]. A study comparing aromatic interactions with salt bridges, demonstrated that the removal of an aromatic ring caused significant hairpin destabilization whereas the replacement of a salt bridge did not cause any major change in peptide stability [10][11][12]. In all these peptides, a consistent edge-to-face geometry was observed indicating that this interaction was preferred despite the conformational flexibility allowed for the side chains of aromatic residues.…”
Section: Aromatic Interactions In Synthetic Peptidesmentioning
confidence: 99%